A composite nanozyme and its preparation method and application

By adopting the structure of composite nanoenzymes, using ferrite as the core material and cerium oxide shell, combined with active targeting ligands, the problem of insufficient magneto-thermal conversion efficiency and catalytic activity of existing nanoenzymes is solved, and efficient glioblastoma treatment is achieved.

CN118750597BActive Publication Date: 2025-03-18Haikou Hospital Affiliated to Xiangya Medical College of Central South University
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410730864.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-06-06
Publication Date
2025-03-18
Estimated Expiration
2044-06-06

AI Technical Summary

Technical Problem

The magnetothermal conversion efficiency and catalytic activity of existing nanoenzymes are insufficient, making it difficult to effectively treat glioblastoma.

Method used

The structure of composite nanoenzymes is adopted, in which the core material is ferrite (MeFe2O4), coated in the cerium oxide shell layer, and coated with active targeting ligands on the outer layer, which is prepared by thermal decomposition reaction to improve magneto-thermal conversion efficiency and catalytic activity.

Benefits of technology

It significantly improves magneto-thermal conversion efficiency and catalytic activity, enhances the therapeutic effect on glioblastoma, and achieves efficient enrichment of nanomaterials in tumor sites.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118750597B_ABST
    Figure CN118750597B_ABST
Patent Text Reader

Abstract

The present invention relates to the field of medical diagnosis technology, and in particular to a composite nanozyme and a preparation method and application thereof. The present invention provides a composite nanozyme, wherein the structure of the composite nanozyme includes a core material and a cerium oxide shell layer coated on the outer layer of the core, wherein the core material is ferrite, and the chemical formula of the ferrite is MeFe2O4, and Me includes a divalent metal ion. The present invention uses three variable valence metal ions to obtain a nanomaterial with higher catalytic activity, and in particular, uses cerium oxide as a shell material to provide activity for catalase and glutathionease.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of medical diagnosis technology, and in particular to a composite nanozyme and a preparation method and application thereof. Background Art

[0002] Gliomas are the most common type of tumors in the central nervous system. Approximately 33% of brain tumors are gliomas, which originate from glial-supported neuronal cells. The current standard first-line treatment for glioblastoma includes surgical resection and postoperative radiotherapy. The high proliferation and invasiveness of glioblastoma and its resistance to radiotherapy and chemotherapy are the main factors affecting the treatment of glioblastoma, which often leads to the recurrence of glioblastoma. Therefore, in the process of tumor treatment, accurate tumor diagnosis is a prerequisite for effective treatment. Through accurate diagnosis, the type, development stage and size of the tumor can be judged, and its impact on surrounding tissues can be evaluated, so as to formulate scientific and reasonable treatment measures. At the same time, timely feedback on the treatment effect of the tumor during or after the treatment of the tumor can help to adjust the treatment plan in time and avoid unnecessary harm to the patient caused by re-administration of the drug.

[0003] Nanobiomedicine is not limited to drug delivery in the treatment of glioblastoma. It is also used to improve the accuracy of diagnosis and early detection capabilities. By using nanoprobes with high specificity and sensitivity, doctors can detect tumors in the early stages of the disease, greatly improving the success rate of treatment. At the same time, nanomaterials also play a role in emerging treatment technologies, such as photothermal therapy, photodynamic therapy, magnetic thermotherapy, sonodynamic therapy and immunotherapy. By accumulating nanoparticles at the tumor and applying light, magnetism, sound and other stimuli to induce tumor cell death, it provides a new strategy for glioblastoma. Nanozymes are a class of nanomaterials with natural enzyme-like catalytic activity. Nanozymes can catalyze the conversion of enzyme substrates into products and follow enzyme kinetics under physiologically relevant conditions. Due to the inherent characteristics of nanomaterials, nanozymes have high stability, large specific surface area and designability, which can overcome the shortcomings of natural enzymes such as instability, high cost, few sources, and easy inactivation in complex environments. Therefore, they have received widespread attention in the fields of biosensing, biomedical imaging, disease treatment and environmental protection. Since the tumor site contains a high content of hydrogen peroxide, peroxide-like nanozymes play an important role in tumor treatment. However, in actual applications, due to the influence of the solid tumor microenvironment such as overexpressed GSH, lower pH and insufficient oxygen content, most nanozymes find it difficult to exert their due therapeutic effects.

[0004] The prior art discloses a bimetallic-organic framework material and its preparation method and application, which utilizes a nanosheet structure to improve the ability to generate reactive oxygen free radicals and enhance the microwave ablation effect of tumors, but the magnetothermal performance conversion efficiency is poor. Summary of the invention

[0005] Therefore, the technical problem to be solved by the present invention is to overcome the defect of poor magnetothermal conversion efficiency of nanozymes in the prior art, thereby providing a composite nanozyme and its preparation method and application.

[0006] Another technical problem to be solved by the present invention is to overcome the defect of low catalytic activity of nanozymes in the prior art, thereby providing a composite nanozyme and a preparation method and application thereof to improve the catalytic activity of the nanozyme.

[0007] On the one hand, the present invention provides a composite nanozyme, the structure of which includes a core and a cerium oxide shell layer coated on the outer layer of the core, wherein the core material is ferrite, the chemical formula of the ferrite is MeFe2O4, and Me includes a divalent metal ion.

[0008] In some embodiments, the divalent metal ions include at least one of manganese ions, zinc ions, copper ions, nickel ions, magnesium ions and cobalt ions.

[0009] In some embodiments, the structure of the composite nanozyme further includes an active targeting ligand coated on the surface of the shell. The active targeting ligand includes at least one of a molecular ligand, a polypeptide ligand and a monoclonal antibody ligand, optionally, the molecular ligand includes at least one of folic acid and hyaluronic acid, and optionally, the polypeptide ligand includes at least one of a transmembrane peptide LinTT1 and a rabies virus glycoprotein RVG.

[0010] In some of the embodiments, the structure of the composite nanozyme further includes a drug disposed on the cerium oxide shell layer. Optionally, the drug includes at least one of an anti-tumor drug and an immune activator.

[0011] On the other hand, the present invention provides a method for preparing a composite nanozyme, comprising the steps of mixing an organic matter containing iron, an organic matter containing a divalent metal and an organic matter containing cerium, and heating the mixture to obtain the composite nanozyme.

[0012] In some embodiments, the heating treatment temperature is 200-300° C., and the heating time is 2-12 hours.

[0013] In some embodiments, the heating treatment includes a thermal decomposition treatment method, which includes the following steps: S1, mixing iron-containing organic matter, divalent metal-containing organic matter and surfactant in the presence of an organic solvent, and heating the mixture in an inert atmosphere to obtain a core material; S2, mixing the core material, cerium-containing organic matter and surfactant, and heating the mixture in an inert atmosphere to obtain a composite nanozyme.

[0014] In some embodiments, the heating treatment step in step S1 and / or step S2 includes reacting at a first temperature for a first time and then heating to a second temperature for a second time.

[0015] In some embodiments, the first temperature is 200-220° C., and the first time is 1-1.5 hours.

[0016] In some embodiments, the second temperature is 290-310° C., and the second time is 0.5-1.5 h.

[0017] In some embodiments, the iron-containing organic compound includes at least one of ferric acetylacetonate, ferrocene, dinonylcarbonyl iron or sodium ferric ethylenediaminetetraacetate.

[0018] In some embodiments, the divalent metal-containing organic compound comprises an acetylacetonate metal complex. Optionally, the divalent metal-containing organic compound comprises at least one of acetylacetonate molybdenum, acetylacetonate manganese, acetylacetonate cobalt, acetylacetonate copper, acetylacetonate nickel or acetylacetonate magnesium.

[0019] In some embodiments, the solvent includes at least one of octadecene, tetradecene or benzyl ether.

[0020] In some embodiments, the cerium-containing organic compound includes cerium acetylacetonate, cerium oxalate or cerium trifluoromethanesulfonate.

[0021] In some embodiments, the surfactant comprises oleic acid.

[0022] In some of the embodiments, before the heating treatment in step S1, the temperature of the mixed solution formed by mixing the iron-containing organic matter, the divalent metal-containing organic matter, oleic acid and the surfactant is raised to 110-120° C. and maintained for 30-60 minutes in an inert atmosphere.

[0023] In some of the embodiments, before the thermal decomposition reaction in step S2, the step also includes a step of heating the mixed solution formed by mixing the core material with the cerium-containing organic matter and oleic acid to 110-120°C and maintaining it for 30-60 minutes in an inert atmosphere. Optionally, before mixing the core material with the cerium-containing organic matter and the surfactant, the temperature of the core material is adjusted to 100-120°C.

[0024] In some embodiments, step S2 also includes a step of solid-liquid separation of the mixture obtained after the thermal decomposition reaction. Optionally, the solid-liquid separation includes the steps of magnetic attraction, washing, and drying. Optionally, the washing step uses an organic solvent, cyclohexane, acetone, chloroform or acetone.

[0025] In some embodiments, the molar ratio of the iron-containing organic matter, the divalent metal-containing organic matter, the surfactant and the organic solvent in step S1 is (1-2):1:(5-10):(50-100).

[0026] In some of the embodiments, the molar ratio of the iron-containing organic matter in step S1 to the cerium-containing organic matter in step S2 is (1-2):(1-2).

[0027] In some of the embodiments, the method for preparing the composite nanozyme further comprises the step of mixing the composite nanozyme solution with an active targeting ligand solution.

[0028] Optionally, the step of mixing the composite nanozyme solution with the active targeting ligand solution includes dropping the active targeting ligand solution into the composite nanozyme solution, oscillating at a speed of 160 to 180 rpm for 10 to 14 hours, and then separating the solid and liquid, and the obtained precipitate is a composite nanozyme connected with an active targeting ligand.

[0029] Optionally, the active targeting ligand solution is dripped into the composite nanozyme solution at a rate of 10 to 12 drops / min;

[0030] Optionally, the solid-liquid separation comprises centrifuging the shaken mixture at 5500-6500 rpm for 8-12 min.

[0031] In some embodiments, the composite nanozyme solution comprises a mixture of the composite nanozyme and an organic solvent, wherein the organic solvent comprises at least one of cyclohexane, chloroform, acetone, toluene or ethanol.

[0032] In some of the embodiments, the active targeting ligand solution comprises a mixture of an active targeting ligand, an alkaline substance and an organic solvent, wherein the alkaline substance comprises sodium hydroxide and the organic solvent comprises at least one of cyclohexane, chloroform, acetone, toluene or ethanol.

[0033] Optionally, the mass ratio of the alkaline substance to the active targeting ligand is 1:(15-30),

[0034] Optionally, the mass ratio of the composite nanozyme to the active targeting ligand is 1:(1-5).

[0035] The composite nanozyme provided by the present invention or the composite nanozyme prepared by the above-mentioned composite nanozyme preparation method has any of the following uses: (1) use in preparing tumor diagnostic reagents; (2) use in preparing tumor treatment products; (3) use in catalyzing the activity of peroxidase; (4) use in catalyzing the activity of glutathione oxidase; (5) use in catalyzing the activity of catalase.

[0036] The technical solution of the present invention has the following advantages:

[0037] 1. A composite nanozyme provided by the present invention comprises a core and a cerium oxide shell layer coated on the outer layer of the core, wherein the core material is ferrite, the chemical formula of the ferrite is MeFe2O4, and Me comprises a divalent metal ion. The composite nanozyme provided by the present invention can improve the magnetothermal conversion efficiency. The present invention utilizes three variable valence metal ions to obtain a nanomaterial with higher catalytic activity, and uses cerium oxide as a shell material to provide activity for catalase and glutathionease.

[0038] 2. A composite nanozyme provided by the present invention, wherein the structure of the composite nanozyme further comprises an active targeting ligand coated on the surface of the shell layer. The present invention coats the outer layer of the composite nanozyme with an active targeting ligand, so that the composite nanozyme has an active targeting function, and can passively target (magnetically target) tumors under the action of a static magnetic field. When the blood-brain barrier is temporarily opened by the heat generated by an external magnetic field, the dual targeting of active targeting and passive targeting can achieve efficient enrichment of nanomaterials at the tumor site.

[0039] 3. The present invention provides a method for preparing a composite nanozyme, comprising the steps of mixing an organic matter containing iron, an organic matter containing divalent metals and an organic matter containing cerium, and obtaining a composite nanozyme after a thermal decomposition reaction. The present invention obtains a composite nanozyme material having a small particle size and uniform distribution by mixing an organic matter containing iron, an organic matter containing divalent metals and an organic matter containing cerium and using a thermal decomposition reaction.

[0040] 4. The present invention provides a method for preparing a composite nanozyme, comprising the following steps: in the presence of an organic solvent, an organic matter containing iron, an organic matter containing divalent metals and a surfactant are mixed, and the mixture is heated in an inert atmosphere to obtain a core material; S2, the core material, the organic matter containing cerium and the surfactant are mixed, and the mixture is heated in an inert atmosphere to obtain a composite nanozyme. The present invention obtains the core material by adopting a staged thermal decomposition method, and then the outer layer of the core material is coated with a shell material by a staged thermal decomposition method. The composite nanozyme obtained has a small particle size, a stable structure, good dispersibility, and good performance in magnetism and catalytic activity.

[0041] 5. The present invention provides a method for preparing a composite nanozyme, wherein the surfactant includes oleic acid. The present invention controls the morphology of the core material and the composite nanozyme by adding a surfactant during the preparation of the core material. At the same time, during the coating process of the core material and the shell material, the present invention uses oleic acid to form an oleic acid complex with each metal ion, and at the same time promotes the metal in the composite nanozyme to become a variable valence metal.

[0042] 6. The present invention provides a method for preparing a composite nanozyme, which has a fast synthesis speed and a simple method. At the same time, the particle size and morphology can be controlled, and large-scale production can be achieved.

[0043] 7. The composite nanozyme provided by the present invention or the composite nanozyme prepared by the composite nanozyme preparation method can be used for tumor diagnosis and preparation of tumor treatment products. Through multiple tumor treatments such as chemodynamic therapy, magnetic heat therapy and ferroptosis, the multifunctionalization of tumor treatment is achieved, breaking through the complex dilemma of traditional multi-modal treatment relying on multi-component materials.

[0044] The composite nanozyme provided by the present invention has excellent paramagnetic properties and can induce local hyperthermia to kill tumor cells under the action of an external alternating electromagnetic field (AMF), thereby achieving magnetic hyperthermia therapy (MHT). This is because the composite nanozyme provided by the present invention has multivalent metal ion pairs, low-valent metal ion pairs (Ce 3+ / Me 2+ / Fe 2+ ) can catalyze excess hydrogen peroxide through the Fenton reaction to produce highly toxic hydroxyl radicals that kill tumor cells, and the generated high-valent metal ion pairs (Ce / 4+ / Me 6+ / Fe 3+ ) can consume excessive glutathione, leading to the inactivation of GPX4, causing a large accumulation of lipid peroxides (LPO) inside the tumor, thereby triggering ferroptosis of tumor cells. At the same time, the valence state transition between the valence metal ion pairs effectively realizes the cascade of its peroxidase and glutathione oxidase.

[0045] In the transition between low-valent and high-valent states of multivalent metals in the composite nanozymes, the catalase catalytic activity of the nanomaterial can catalyze hydrogen peroxide to produce oxygen, alleviate the hypoxic state inside the tumor, amplify oxidative stress, and further improve the effects of chemodynamic therapy and ferroptosis therapy. At the same time, the magnetothermal effect can further enhance the multiple enzyme catalytic activity of the nanoplatform and further enhance its therapeutic effect.

[0046] In addition, the Ce and Fe elements rich in the nano-diagnostic and therapeutic platform give it the ability of T1 / T2 dual-modality magnetic resonance imaging, which can provide more accurate information for the diagnosis and treatment of glioblastoma. BRIEF DESCRIPTION OF THE DRAWINGS

[0047] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0048] Figure 1 This is a SEM image of the composite nanozyme coated with an active targeting ligand prepared in Example 1 of the present invention;

[0049] Figure 2 This is a particle size diagram of the composite nanozyme coated with an active targeting ligand prepared in Example 1 of the present invention;

[0050] Figure 3 This is the XRD pattern of the composite nanozyme coated with active targeting ligand prepared in Example 1 of the present invention;

[0051] Figure 4 This is the infrared spectrum of the composite nanozyme coated with active targeting ligand prepared in Example 1 of the present invention;

[0052] Figure 5 This is a graph of the magnetothermal performance of the core material prepared in Example 1 of the present invention and the composite nanozyme coated with an active targeting ligand;

[0053] Figure 6 This is a graph of the magnetothermal performance of the composite nanozyme coated with an active targeting ligand prepared in Example 1 of the present invention at different mass concentrations;

[0054] Figure 7 This is a graph showing the specific loss rate of the composite nanozymes coated with active targeting ligands prepared in Examples 1, 13-14 and Comparative Examples 1-6 of the present invention;

[0055] Figure 8 is a graph showing the results of the catalytic activity of peroxidase under different treatment conditions in Experimental Example 3 of the present invention;

[0056] Fig. 9 is a graph showing the catalytic activity of catalase under different treatment conditions in Experimental Example 4 of the present invention;

[0057] Fig.10 is a graph showing the catalytic activity of glutathione oxide under different treatment conditions in Experimental Example 5 of the present invention;

[0058] Fig.11 It is the T1-weighted imaging image in Experimental Example 6 of the present invention;

[0059] Fig.12 It is the T2-weighted imaging image in Experimental Example 6 of the present invention;

[0060] Fig.13 This is a graph showing the results of composite nanozymes crossing the BBB under different treatment conditions in Experimental Example 7 of the present invention;

[0061] Fig.14 This is a graph showing the cell survival rate results under different treatment conditions in Experimental Example 8 of the present invention;

[0062] Fig.15 is a graph showing the results of glutathione content under different treatment conditions in Experimental Example 8 of the present invention;

[0063] Fig.16This is a graph showing the results of lipid peroxide content under different treatment conditions in Experimental Example 8 of the present invention;

[0064] Fig.17 This is a graph showing changes in T1 and T2 signals of mouse brain tumors under different treatment conditions in Experimental Example 9 of the present invention;

[0065] Fig.18 This is a graph showing changes in bioluminescent signals in the brain of mice under different treatment conditions in Experimental Example 9 of the present invention;

[0066] Fig.19 This is a staining diagram of mouse brain slices under different treatment conditions in Experimental Example 9 of the present invention. DETAILED DESCRIPTION

[0067] The following examples are provided for a better understanding of the present invention, but are not intended to limit the best mode of implementation, nor to limit the content and protection scope of the present invention. Any product identical or similar to the present invention obtained by anyone under the inspiration of the present invention or by combining the features of the present invention with other prior arts shall fall within the protection scope of the present invention.

[0068] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.

[0069] Example 1

[0070] This embodiment provides a method for preparing a composite nanozyme, and the specific steps and parameters are as follows:

[0071] (1) 1.0 mmol of molybdenum acetylacetonate and 2 mmol of ferric acetylacetonate were added to a 100 mL three-necked flask, and then 3 mL of oleic acid and 20 mL of octadecene were added and mixed to obtain a mixed solution A;

[0072] (2) under the protection of nitrogen, the temperature of the mixed solution A was raised to 110° C. at a heating rate of 5° C. / min, maintained for 30 minutes, then raised to 200° C. at a heating rate of 5° C. / min, maintained for 1.5 hours, and then raised to 300° C. at a heating rate of 10° C., maintained for 1.5 hours, to obtain a core material;

[0073] (3) dispersing 1 mmol of cerium acetylacetonate in 3 mL of oleic acid to form a cerium acetylacetonate mixed solution, lowering the temperature of the core material obtained in step (2) to 100° C., and then adding the cerium acetylacetonate mixed solution thereto to obtain a mixed solution B;

[0074] (4) under the protection of nitrogen, the temperature of the mixed solution B was raised to 110°C at a heating rate of 5°C / min, maintained for 30 minutes, then raised to 200°C at a heating rate of 5°C / min, maintained for 1 hour, and then raised to 300°C at a heating rate of 10°C. After keeping the temperature for 1.5 hours, the temperature was lowered to room temperature;

[0075] (5) The reaction solution in the three-necked flask whose temperature has dropped to room temperature is transferred to a beaker and a neodymium magnet is placed on one side of the beaker. The reaction solution is removed with a pipette, and the black solid adsorbed on one side of the beaker is washed three times with acetone. The solvent is then removed in an oven to obtain a black powder, which is the composite nanozyme.

[0076] (6) Take 10 mg of the composite nanozyme prepared in step (5) and add it to a 50 mL single-mouth bottle containing 5 mL of anhydrous ethanol, and use a 1200W ultrasonic crusher to ultrasonically disperse to obtain a composite nanozyme solution; disperse 30 mg of folic acid in 2 mL of anhydrous ethanol, and then add 1 mg of NaOH to it, and ultrasonically dissolve it completely to obtain a folic acid solution; add the folic acid solution to the composite nanozyme solution at a drop rate of 10 drops / minute, seal the single-mouth bottle and place it in an oscillator at 37°C and 180 rpm for 12 hours. After the oscillation is completed, centrifuge at 6000 rpm / min for 10 minutes to obtain a solid precipitate, that is, a composite nanozyme coated with an active targeting ligand, and disperse the collected solid precipitate in 5 mL of ultrapure water for dispersion and storage.

[0077] The composite nanozyme coated with active targeting ligand prepared in step (6) was subjected to SEM and XRD scanning respectively, and the results are shown in Figure 1-4 , among which, see Figure 1 It can be seen that the composite nanozyme coated with active targeting ligand prepared in this example is a spherical structure and is dispersed relatively evenly. Figure 2 It can be seen that the composite nanozyme coated with active targeting ligand prepared in this example has a particle size of 38.6 nm and a dispersibility index (PDI) of 0.269, which has excellent dispersibility.

[0078] See also Figure 3 It can be seen that the composite nanozyme (MoFe2O4@CeO2 / FA) coated with an active targeting ligand prepared in this embodiment showed obvious crystal diffraction peaks at 2θ=28.5°, 33.1°, 47.8°, 56.3°, and 76.7°, corresponding to the standard card of CeO2 (CeO2: #43-1002). At the same time, the crystal diffraction peaks at 2θ=18.1, 29.7, 35.0, 36.6, 42.5, 52.7, 56.2, and 61.7° were completely consistent with the spinel structured ferrite nanomaterial (MFe2O4).

[0079] See also Figure 4 It can be seen that the composite nanozyme coated with active targeting ligand prepared in this embodiment has the peaks at 3541, 3438 and 3325 cm -1 Typical -OH and -NH2 infrared characteristic peaks appear, 1680-1750cm -1 The infrared characteristic peak is attributed to the C=O bond. -1 Typical infrared peaks of metal oxide bonds appeared. These results demonstrated the successful preparation of the composite nanozyme coated with active targeting ligands in this example.

[0080] Example 2

[0081] This embodiment provides a method for preparing a composite nanozyme, and the specific steps and parameters are as follows:

[0082] (1) 1 mmol of molybdenum acetylacetonate and 1 mmol of ferric acetylacetonate were added to a 100 mL three-necked flask, and then 1.6 mL of oleic acid and 16.5 mL of octadecene were added and mixed to obtain a mixed solution A;

[0083] (2) under the protection of nitrogen, the temperature of the mixed solution A was raised to 120° C. at a heating rate of 10° C. / min, maintained for 30 minutes, then raised to 220° C. at a heating rate of 5° C. / min, maintained for 1 hour, and then raised to 310° C. at a heating rate of 10° C., maintained for 0.5 hour, to obtain a core material;

[0084] (3) dispersing 2 mmol of cerium acetylacetonate in 3 mL of oleic acid to form a cerium acetylacetonate mixed solution, lowering the temperature of the core material obtained in step (2) to 120° C., and then adding the cerium acetylacetonate mixed solution thereto to obtain a mixed solution B;

[0085] (4) maintaining the temperature of the mixed solution B at 120°C for 30 minutes under the protection of nitrogen, then increasing the temperature to 210°C at a heating rate of 5°C / min and maintaining it for 1 hour, increasing the temperature to 290°C at a heating rate of 10°C and maintaining it for 1.5 hours, and then decreasing the temperature to room temperature;

[0086] (5) The reaction solution in the three-necked flask whose temperature has dropped to room temperature is transferred to a beaker and a neodymium magnet is placed on one side of the beaker. The reaction solution is removed with a pipette, and the black solid adsorbed on one side of the beaker is washed three times with acetone. The solvent is then removed in an oven to obtain a black powder, which is the composite nanozyme.

[0087] (6) Take 10 mg of the composite nanozyme prepared in step (5) and add it to a 50 mL single-mouth bottle containing 5 mL of cyclohexane, and use a 1200W ultrasonic crusher to ultrasonically disperse to obtain a composite nanozyme solution; disperse 10 mg of hyaluronic acid in 2 mL of cyclohexane, add 0.5 mg of NaOH thereto, and ultrasonically dissolve it completely to obtain a hyaluronic acid solution; add the hyaluronic acid solution to the composite nanozyme solution at a drop rate of 10 drops / minute, seal the single-mouth bottle and place it in an oscillator at 37 ° C and 180 rpm for 12 hours. After the oscillation is completed, centrifuge at 6000 rpm / min for 10 minutes to obtain a solid precipitate, that is, a composite nanozyme coated with an active targeting ligand, and disperse the collected solid precipitate in 5 mL of ultrapure water for dispersion and preservation.

[0088] Example 3

[0089] This embodiment provides a method for preparing a composite nanozyme, and the specific steps and parameters are as follows:

[0090] (1) 1.0 mmol of molybdenum acetylacetonate and 2 mmol of ferric acetylacetonate were added to a 100 mL three-necked flask, and then 3 mL of oleic acid and 32 mL of octadecene were added and mixed to obtain a mixed solution A;

[0091] (2) under the protection of nitrogen, the temperature of the mixed solution A was raised to 120° C. at a heating rate of 10° C. / min, maintained for 30 minutes, then raised to 220° C. at a heating rate of 5° C. / min, maintained for 1 hour, and then raised to 310° C. at a heating rate of 10° C., maintained for 0.5 hour, to obtain a core material;

[0092] (3) dispersing 2 mmol of cerium acetylacetonate in 5 mL of oleic acid to form a cerium acetylacetonate mixed solution, lowering the temperature of the core material obtained in step (2) to 120° C., and then adding the cerium acetylacetonate mixed solution thereto to obtain a mixed solution B;

[0093] (4) maintaining the temperature of the mixed solution B at 120°C for 30 minutes under the protection of nitrogen, then increasing the temperature to 210°C at a heating rate of 5°C / min and maintaining it for 1 hour, increasing the temperature to 290°C at a heating rate of 10°C and maintaining it for 1.5 hours, and then decreasing the temperature to room temperature;

[0094] (5) The reaction solution in the three-necked flask whose temperature has dropped to room temperature is transferred to a beaker and a neodymium magnet is placed on one side of the beaker. The reaction solution is removed with a pipette, and the black solid adsorbed on one side of the beaker is washed three times with acetone. The solvent is then removed in an oven to obtain a black powder, which is the composite nanozyme.

[0095] (6) Take 10 mg of the composite nanozyme prepared in step (5) and add it to a 50 mL single-mouth bottle containing 5 mL of acetone, and use a 1200W ultrasonic crusher to perform ultrasonic dispersion to obtain a composite nanozyme solution; disperse 50 mg of the transmembrane peptide LinTT1 in 2 mL of acetone, and then add 3.3 mg of NaOH to it, and ultrasonically dissolve it completely to obtain a transmembrane peptide LinTT1 solution; add the transmembrane peptide LinTT1 solution to the composite nanozyme solution at a drop rate of 10 drops / minute, seal the single-mouth bottle and place it in an oscillator at 37°C and 180 rpm for 12 hours. After the oscillation is completed, centrifuge at 6000 rpm / min for 10 minutes to obtain a solid precipitate, that is, a composite nanozyme coated with an active targeting ligand, and disperse the collected solid precipitate in 5 mL of ultrapure water for dispersion and storage.

[0096] Example 4

[0097] This embodiment provides a method for preparing a composite nanozyme, and the specific steps and parameters are as follows:

[0098] (1) 1.0 mmol of manganese acetylacetonate and 2 mmol of ferrocene were added to a 100 mL three-necked flask, and then 3 mL of oleic acid and 10 mL of tetradecene were added and mixed to obtain a mixed solution A;

[0099] The remaining steps and parameters are the same as in Example 1

[0100] Example 5

[0101] This embodiment provides a method for preparing a composite nanozyme, and the specific steps and parameters are as follows:

[0102] (1) 1.0 mmol of cobalt acetylacetonate and 2 mmol of dinonyl iron carbonyl were added to a 100 mL three-necked flask, and then 3 mL of oleic acid and 10 mL of dibenzyl ether were added and mixed to obtain a mixed solution A;

[0103] The remaining steps are the same as those in Example 1.

[0104] Example 6

[0105] This embodiment provides a method for preparing a composite nanozyme, and the specific steps and parameters are as follows:

[0106] (1) 1.0 mmol of copper acetylacetonate and 2 mmol of iron acetylacetonate were added to a 100 mL three-necked flask, and then 3 mL of oleic acid and 20 mL of octadecene were added and mixed to obtain a mixed solution A;

[0107] The remaining steps are the same as those in Example 1.

[0108] Example 7

[0109] This embodiment provides a method for preparing a composite nanozyme, and the specific steps and parameters are as follows:

[0110] (1) 1.0 mmol of nickel acetylacetonate and 2 mmol of sodium ferric ethylenediaminetetraacetate were added to a 100 mL three-necked flask, and then 3 mL of oleic acid and 20 mL of octadecene were added and mixed to obtain a mixed solution A;

[0111] The remaining steps are the same as those in Example 1.

[0112] Example 8

[0113] This embodiment provides a method for preparing a composite nanozyme, and the specific steps and parameters are the same as those in Example 1, except that an equimolar amount of magnesium acetylacetonate is used to replace molybdenum acetylacetonate in step (1).

[0114] Example 9

[0115] This embodiment provides a method for preparing a composite nanozyme, and the specific steps and parameters are the same as those in Example 1, except that an equimolar amount of cerium oxalate is used to replace cerium acetylacetonate in step (3).

[0116] Example 10

[0117] This embodiment provides a method for preparing a composite nanozyme, and the specific steps and parameters are the same as those in Example 1, except that an equimolar amount of cerium trifluoromethanesulfonate is used to replace cerium acetylacetonate in step (3).

[0118] Embodiment 11

[0119] This embodiment provides a method for preparing a composite nanozyme. The specific steps and parameters are the same as those in Example 1, except that an equal mass of rabies virus glycoprotein RVG is used to replace folic acid in step (6), and an equal volume of chloroform is used to replace anhydrous ethanol, that is, 30 mg of rabies virus glycoprotein RVG is dispersed in 2 mL of chloroform.

[0120] Example 12

[0121] This embodiment provides a method for preparing a composite nanozyme, and the specific steps and parameters are the same as those in Example 1, except that an equal volume of toluene is used instead of anhydrous ethanol to disperse the active targeting ligand in step (6), that is, 30 mg of folic acid is dispersed in 2 mL of toluene.

[0122] Embodiment 13

[0123] This embodiment provides a method for preparing a composite nanozyme, and the specific steps and parameters are as follows:

[0124] (1) adding 1.0 mmol of molybdenum acetylacetonate and 2 mmol of ferric acetylacetonate to a 100 mL three-necked flask, adding 3 mL of oleic acid and 20 mL of octadecene, and mixing to obtain a mixed solution A, dispersing 1 mmol of cerium acetylacetonate in 3 mL of oleic acid to form a cerium acetylacetonate mixed solution, and mixing the cerium acetylacetonate mixed solution with the mixed solution A to obtain a mixed solution B;

[0125] (2) under the protection of nitrogen, the temperature of the mixed solution B was raised to 110°C at a heating rate of 5°C / min, maintained for 30 minutes, then raised to 200°C at a heating rate of 5°C / min, maintained for 1 hour, and then raised to 300°C at a heating rate of 10°C. After keeping the temperature for 1.5 hours, the temperature was lowered to room temperature;

[0126] The remaining steps are the same as those in Example 1.

[0127] After testing, the composite nanozyme coated with active targeting ligand in this embodiment has a spherical morphology and a particle size of 38.7 nm.

[0128] Embodiment 14

[0129] The present embodiment provides a method for preparing a composite nanozyme, and the specific steps and parameters are the same as those in Example 10, except that in step (2), the temperature of the mixed solution B is raised to 110°C at a heating rate of 5°C / min under the protection of nitrogen, maintained for 30 minutes, and then the temperature is raised to 200°C at a heating rate of 5°C / min, maintained for 12 hours, and then the temperature is lowered to room temperature.

[0130] After testing, the composite nanozyme coated with active targeting ligand in this embodiment has an irregular spherical morphology and a particle size of 54.6 nm.

[0131] Comparative Example 1

[0132] This comparative example provides a method for preparing a composite nanozyme, and the specific steps and parameters are the same as those in Example 1, except that step (3) and step (4) are not included, that is, folic acid is coated on the outer layer of the core material to obtain the composite nanozyme.

[0133] Comparative Example 2

[0134] This comparative example provides a method for preparing a composite nanozyme, and the specific steps and parameters are the same as those in Example 1, except that step (1) does not contain molybdenum acetylacetonate, that is, 2 mmol of ferric acetylacetonate is added to a 100 mL three-necked flask, and then 3 mL of oleic acid and 20 mL of octadecene are added and mixed to obtain a mixed solution A.

[0135] Comparative Example 3

[0136] This comparative example provides a method for preparing a composite nanozyme, and the specific steps and parameters are the same as those in Example 1, except that an equimolar amount of aluminum acetylacetonate is used to replace molybdenum acetylacetonate in step (1).

[0137] Comparative Example 4

[0138] This comparative example provides a method for preparing a composite nanozyme, and the specific steps and parameters are the same as those in Example 1, except that an equimolar amount of molybdenum nitrate is used to replace molybdenum acetylacetonate in step (1).

[0139] Comparative Example 5

[0140] This comparative example provides a method for preparing a composite nanozyme, and the specific steps and parameters are the same as those in Example 1, except that an equimolar amount of iron nitrate is used to replace the iron acetylacetonate in step (1).

[0141] Comparative Example 6

[0142] This comparative example provides a method for preparing a composite nanozyme, and the specific steps and parameters are the same as those in Example 1, except that an equimolar amount of cerium nitrate is used to replace the cerium acetylacetonate in step (3).

[0143] Experimental Example 1

[0144] The magnetic properties of the core material prepared in step (2) of Example 1 and the composite nanozyme coated with the active targeting ligand prepared in step (6) were detected using a vibrating sample magnetometer (the magnetometer model was Lake shore 7404, ±2T, USA).

[0145] Test results see Figure 5 It can be seen that no obvious hysteresis was observed in the hysteresis loops of the core material and the composite nanozyme coated with the active targeting ligand, indicating that the core material and the composite nanozyme coated with the active targeting ligand prepared by the present invention both have superparamagnetism, indicating that both can respond to the static magnetic field and have the potential for application in magnetic targeting in vivo. Furthermore, the saturation magnetization intensity of the core material is 49.4emu / g. Under the same core material equivalent, the saturation magnetization intensity of the composite nanozyme coated with the active targeting ligand reaches 64.7emu / g, indicating that the composite nanozyme coated with the active targeting ligand prepared by the present invention has higher magnetothermal performance.

[0146] Experimental Example 2

[0147] The composite nanozyme coated with an active targeting ligand obtained in step (6) of Example 1 was dispersed in pure water, and composite nanozyme aqueous solutions with mass concentrations of 0 mg / mL, 0.125 mg / mL, 0.25 mg / mL, 0.5 mg / mL, 1 mg / mL, 2 mg / mL, and 3 mg / mL were prepared respectively. The magnetothermal properties of the composite nanozyme aqueous solutions with different mass concentrations were detected in an electromagnetic field with a field strength of 1.38 mT and a frequency of 498 kHz. The solution temperature was measured using an infrared thermal imaging device, Fluke TiS55, as an indicator of the secondary thermal performance.

[0148] Results Figure 6 It can be seen that the temperature change of pure water in the electromagnetic field within 10 minutes can be ignored, indicating that the electromagnetic field has little effect on water, while the composite nanozyme aqueous solutions of different mass concentrations can be observed to have obvious temperature changes within 10 minutes. When the mass concentration of the composite nanozyme aqueous solution is 3.0 mg / mL, its temperature rises from room temperature to 68.3°C within 10 minutes. Even in a lower concentration range, that is, when the mass concentration of the composite nanozyme aqueous solution is 0.125 mg / mL, obvious temperature changes can be observed, which shows that the composite nanozyme prepared by the present invention has excellent magnetothermal properties and can kill tumor cells by magnetothermal effect.

[0149] The heat generation efficiency of nanoparticles directly affects the effect of magnetic hyperthermia. The specific loss power (SLP) is usually used to measure the ability of magnetic nanoparticles of a certain mass or volume to convert magnetothermally within a certain period of time. The higher the SLP value, the stronger the magnetic induction heating ability and the higher the magnetothermal conversion efficiency. The unit of SLP is W / g. Therefore, in this embodiment, the composite nanozymes coated with active targeting ligands prepared in Examples 1, 13-14 and Comparative Examples 1-6 are used to prepare a composite nanozyme aqueous solution with a concentration of 3 mg / mL with pure water. The magnetothermal properties of each composite nanozyme aqueous solution are detected in an electromagnetic field with a field strength of 1.38 mT and a frequency of 498 kHz. The solution temperature is measured using an infrared thermal imaging device Fluke TiS55 as an indicator of the magnetothermal performance. The specific loss power SLP is obtained according to the following formula (1).

[0150]

[0151] Among them, m Fe Indicates the iron content in the sample being tested, C H2O The heat required for each 1°C increase in temperature is approximately 4.184 JK. -1 g -1 , m H2O represents the mass of water in the solution, d T / d tIt represents the slope of temperature versus time over a short period of time.

[0152] Results Figure 7 It can be seen that the composite nanozyme prepared in the embodiment of the present invention has a strong magnetic induction heating ability.

[0153] Experimental Example 3

[0154] The catalytic activity of the composite nanozymes coated with active targeting ligands prepared in Examples 1, 13-14 and Comparative Examples 1-6 on peroxidase was determined by 3,3',5,5'-tetramethylbenzidine (TMB) oxidation method. The specific detection method is as follows: each group of reagents is prepared, and the ultraviolet absorption value of each group of reagents at 652nm is recorded by an ultraviolet spectrophotometer. In this experimental example, TMB was purchased from Aladdin, item number T100415-25g,

[0155] Among them, group 1 was prepared by adding 10 μL of aqueous hydrogen peroxide solution (10 mM) to 10 μL of DMSO solution containing TMB (20 mg / mL) and mixing to obtain reagent 1;

[0156] Group 2 was prepared by adding 10 μL of aqueous hydrogen peroxide solution (10 mM) to 10 μL of DMSO solution containing TMB (20 mg / mL), mixing the mixture, placing the mixture in a magnetic thermal device, and turning on the magnetic thermal device (f=498 kHz, 1.38 mT) for 10 min to obtain reagent 2;

[0157] Group 3 is to add 100 μL of an aqueous solution of the composite nanozyme coated with an active targeting ligand prepared in Example 1 containing 1 mg / mL to 840 μL of an acetic acid and sodium acetate buffer solution at pH = 4.5, and then add 10 μL of a DMSO solution containing TMB (20 mg / mL) and 10 μL of an aqueous hydrogen peroxide solution (10 mM), and mix well to obtain reagent 3;

[0158] Group 4 is prepared by adding 100 μL of the composite nanozyme coated with the active targeting ligand prepared in Example 1 containing 1 mg / mL to 840 μL of acetic acid and sodium acetate buffer solution at pH = 4.5, adding 10 μL of DMSO solution containing TMB (20 mg / mL) and 10 μL of aqueous hydrogen peroxide solution (10 mM), mixing, placing in a magnetic thermal device, and turning on the magnetic thermal device (f = 498 kHz, 1.38 mT) for 10 min to obtain reagent 4.

[0159] Results Figure 8It can be seen that in the presence of hydrogen peroxide, the absorbance of the composite nanozyme coated with active targeting ligand prepared in Example 1 of the present invention at 654nm is significantly improved, which indicates that the composite nanozyme of the present invention can catalyze hydrogen peroxide to produce hydroxyl radicals through a Fenton-like reaction. In particular, in an electromagnetic field with a field strength of 1.38mT and a frequency of 498kHz, the absorbance of reagent 4 is significantly improved, which further proves that the magnetocaloric effect can effectively enhance the peroxidase catalytic activity of the composite nanozyme.

[0160] The reagents of the composite nanozymes coated with active targeting ligands prepared in Examples 1, 13-14 and Comparative Examples 1-6 were obtained by respectively adopting the methods of Group 3 and Group 4, and the changes in the absorbance values ​​of each reagent at 652 nm were measured to obtain the Michaelis-Menten equation, and the Michaelis constant K of the composite nanozymes coated with active targeting ligands prepared in Examples 1, 13-14 and Comparative Examples 1-6 was obtained according to the following formula (2) and formula (3): M ,

[0161] V=(Vmax×[S]) / (K M +[S]); Formula (2)

[0162] V = ΔA / (Δt×ε×l); Formula (3)

[0163] Where V is the initial reaction rate; [S] is the substrate concentration; ΔA is the change in absorbance; Δt represents the initial reaction time (s); ε is the molar absorption coefficient of the colorimetric substrate XTMB, usually 39000M; 1 is the path length of light propagation in the cuvette (cm).

[0164] As shown in Table 1, compared with Comparative Examples 1-6, the embodiments of the present invention perform well in peroxidase activity, especially after applying an external magnetic field, the catalytic performance of peroxidase activity is better, but the composite nanoenzyme materials prepared in Examples 8 and 9 will cause phase separation, and the enzyme catalytic performance is reduced.

[0165] Experimental Example 4

[0166] The catalytic activity of the composite nanozymes coated with active targeting ligands prepared in Examples 1, 13-14 and Comparative Examples 1-6 on catalase in the presence of hydrogen peroxide was detected by a dissolved oxygen meter (Orion Lab Star DO113 DO). The specific detection steps are as follows: prepare each group of reagents, and then record the reading of the dissolved oxygen meter after every 30 seconds for a total of 10 minutes, wherein,

[0167] Group 1 is to take 30wt% H2O2 aqueous solution and prepare H2O2 to a final concentration of 1.0mM as reagent 1;

[0168] Group 2 is to take a 30wt% H2O2 aqueous solution, configure the H2O2 final concentration to 1.0mM, place it in a magnetic thermal device, and turn on the magnetic thermal device (f = 498kHz, 1.38mT) for 10min to obtain reagent 2;

[0169] Group 3 is 4 mg of the composite nanozyme coated with active targeting ligand prepared in Example 1, which is ultrasonically dispersed into a 50 mL centrifuge tube containing 20 mL of pH = 7.4 PBS buffer solution, and the composite nanozyme prepared in Example 1 is added to make the final concentration of the composite nanozyme 0.2 mg / mL, and a 30 wt% H2O2 aqueous solution is added to each group of reagents to make the final concentration of H2O2 in each group of reagents reach 1.0 mM, to obtain reagent 3;

[0170] Group 4 is 4 mg of the composite nanozyme coated with the active targeting ligand prepared in Example 1, which is ultrasonically dispersed into a 50 mL centrifuge tube containing 20 mL of pH = 7.4 PBS buffer solution, and the composite nanozyme prepared in Example 1 is added to make the final concentration of the composite nanozyme 0.2 mg / mL, and a 30wt% H2O2 aqueous solution is added to each group of reagents to make the final concentration of H2O2 in each group of reagents reach 1.0mM, and placed in a magnetic thermal device, and the magnetic thermal device (f = 498kHz, 1.38mT) is turned on for 10min to obtain reagent 4;

[0171] Results Fig. 9 It can be seen that in the presence of H2O2 (1mM), the generation of oxygen was detected in the aqueous solution containing the composite nanozyme, indicating that the composite nanozyme can catalyze hydrogen peroxide to produce oxygen. Furthermore, in the electromagnetic field, more oxygen was detected, indicating that the magnetothermal effect can effectively enhance the catalytic activity of the composite nanozyme on catalase.

[0172] The methods of Group 3 and Group 4 were used to obtain reagents of composite nanozymes coated with active targeting ligands prepared in Examples 1, 13-14 and Comparative Examples 1-6, respectively. The readings of the dissolved oxygen meter were then recorded every 30 seconds for a total of 10 minutes. The results are shown in Table 1. It can be seen that compared with Comparative Examples 1-6, the composite nanozymes prepared in the embodiments of the present invention can catalyze hydrogen peroxide to produce more oxygen, which proves that the composite nanozymes prepared in the embodiments of the present invention have good activity in catalyzing hydrogen peroxide.

[0173] Experimental Example 5

[0174] The catalytic activity of the composite nanozymes coated with active targeting ligands prepared in Examples 1, 13-14 and Comparative Examples 1-6 on glutathione oxidase was determined. The specific detection method was as follows: each group of reagents was configured, and the absorption value of each reagent was recorded by a full-band microplate luminescence detector using an ultraviolet spectrophotometer. In this experimental example, glutathione (GSH) was purchased from McLean, item number R917465-25g, and 5,5'-dithiobis(2-nitrobenzoic acid) (DTNB) was purchased from Aladdin, item number D105559-10g;

[0175] Group 1: 50 μL of GSH (2.0 mM) aqueous solution was added to a 1.5 mL centrifuge tube containing 900 μL of pH = 4.5 buffer solution, mixed evenly, centrifuged at 9000 rpm for 5 min, 190 μL of supernatant was added to 10 μL of DTNB (4 mg / mL) DMSO solution, mixed thoroughly, and waited for 10 min to obtain reagent 1;

[0176] Group 2: 50 μL of GSH (2.0 mM) aqueous solution was added to a centrifuge tube containing 1.5 mL of 900 μL of pH = 4.5 buffer solution, mixed evenly, placed in a magnetic thermal device, turned on the magnetic thermal device (f = 498 kHz, 1.38 mT) for 10 min, and after the magnetic thermal device was completed, centrifuged at 9000 rpm for 5 min, 190 μL of the supernatant was taken and added with 10 μL of DTNB (4 mg / mL) DMSO solution, mixed thoroughly, and waited for 10 min to obtain reagent 2;

[0177] Group 3: 50 μL of the composite nanozyme (4 mg / mL) solution and 50 μL of the GSH (2.0 mM) aqueous solution prepared in Example 1 were added to a 1.5 mL centrifuge tube containing 900 μL of pH=4.5 buffer solution, mixed evenly, centrifuged at 9000 rpm for 5 min, 190 μL of the supernatant was added with 10 μL of DTNB (4 mg / mL) DMSO solution, mixed thoroughly, and waited for 10 min to obtain reagent 3;

[0178] Group 4 is prepared by adding 50 μL of the composite nanozyme (4 mg / mL) solution and 50 μL of the GSH (2.0 mM) aqueous solution prepared in Example 1 into a centrifuge tube containing 1.5 mL of 900 μL of pH=4.5 buffer solution, mixing evenly, placing in a magnetic thermal device, turning on the magnetic thermal device (f=498 kHz, 1.38 mT) for 10 min, and after the magnetic thermal end, centrifuging at 9000 rpm for 5 min, taking 190 μL of the supernatant, adding 10 μL of DTNB (4 mg / mL) DMSO solution, mixing thoroughly, and waiting for 10 min to obtain reagent 4;

[0179] See also Fig.10It can be seen that when the composite nanozyme is added to the mixed solution of DTNB and GSH, its absorption value at 435nm is significantly reduced, indicating that the composite nanozyme has the ability to consume GSH. In an electromagnetic field with a field strength of 1.38mT and a frequency of 498kHz, the absorbance of the mixed solution is significantly reduced, which further proves that the magnetothermal effect can effectively enhance the catalytic activity of the composite nanozyme on glutathione oxidase.

[0180] The reagents of the composite nanozymes coated with active targeting ligands prepared in Examples 1, 13-14 and Comparative Examples 1-6 were obtained by respectively adopting the methods of Group 3 and Group 4, and the changes in the absorbance values ​​of each reagent at 412 nm were measured to obtain the Michaelis-Menten equation, and the Michaelis constant K of the composite nanozymes coated with active targeting ligands prepared in Examples 1, 13-14 and Comparative Examples 1-6 was obtained according to the following formulas (3) and (4): M ,

[0181]

[0182] V = ΔA / (Δt×ε×l); Formula (3)

[0183] Where V is the initial reaction rate; [S] is the substrate concentration; ΔA is the change in absorbance; Δt represents the initial reaction time (s); ε is the molar absorption coefficient of the colorimetric substrate TNB, usually 13600M; 1 is the path length of light propagation in the cuvette (cm).

[0184] The results are shown in Table 1. It can be seen that compared with comparative examples 1-6, the composite nanozyme prepared in the embodiment of the present invention has good glutathione oxide catalytic activity.

[0185] Table 1 Catalytic activity of composite nanozymes

[0186]

[0187] Note: K M is the enzyme activity parameter, the smaller the value, the higher the enzyme activity; there is no activity evaluation parameter for catalase activity, so it can be evaluated by oxygen production. The above experiments show that magnetic heat can effectively enhance the activity of nanozymes.

[0188] Experimental Example 6

[0189] The T1- and T2-weighted imaging capabilities of the nanoparticles were evaluated using a medical magnetic resonance imaging system.

[0190] According to the preparation method of Example 1, 0mM, 0.01mM, 0.02mM, 0.0125mM, 0.025mM, 0.05mM, 0.1mM, 0.2mM, and 0.4mM of ferric acetylacetonate were used to prepare composite nanozymes, and the prepared composite nanozymes were added to 1.5wt% agarose gel, heated and ultrasonically dispersed to make it uniform, and then cooled and solidified. After being sealed and fixed, they were loaded into a small animal imaging coil with a diameter of 5cm, and the samples were scanned using T1-Mapping and T2-Mapping sequences. The parameters were set as follows: T2-Mapping repetition time TR = 4000ms, echo time TE = 45ms. T2-Mapping repetition time TR = 500ms, TE = 14ms.

[0191] Results Fig.11 It can be seen that in the T1-weighted imaging, as the iron content increases, the brightness of the image gradually changes. By measuring its relaxation time, the longitudinal relaxation rate (r1) is obtained by fitting the relaxation time and concentration, that is, it reaches 7.85mM -1 s -1 , higher than the current commercial T1 MRI contrast agent.

[0192] The T2-MAP sequence was used to further determine the T2-MRI imaging capability of the composite nanozyme. Fig.12 As shown in the T1-weighted imaging, as the iron content increases, the brightness of the image gradually darkens. Its transverse relaxation rate (r2) is 110.9mM -1 s -1 .

[0193] The above results indicate that the composite nanozyme prepared in the present invention can be used as a T1 / T2 dual-modality contrast agent, which can provide assistance for the precise diagnosis of tumors.

[0194] Experimental Example 7

[0195] The ability of the composite nanozyme to break through the BBB was determined by the Transwell cell culture method. The specific experimental method is as follows:

[0196] In Transwell (Corning The in vitro BBB model was constructed by culturing neural endothelial cells bEnd.3 (from the American Type Culture Collection - The Global Bioresource Center, ATCC) in the upper chamber of a 24-well plate and culturing GL261 cells (from the American Type Culture Collection) in the lower chamber;

[0197] When the transendothelial cell resistance of the upper bEnd.3 cells reaches 200Ω / cm 2When the composite nanozyme solution labeled with rhodamine B was added (wherein the mass concentration of the composite nanozyme was 200 μg / mL, the mass ratio of rhodamine B to the composite nanozyme was 10 μg:1 mg, and the composite nanozyme solution was prepared using PBS buffer), the upper chamber was placed in an electromagnetic field with a field strength of 1.38 mT and a frequency of 498 kHz for heating for 10 minutes;

[0198] The red fluorescent signal in the lower layer of cells was observed by confocal microscopy to evaluate the ability of the composite nanozyme to cross the BBB.

[0199] The results are as follows Fig.13 As shown, A1 is a blue cell nucleus marked at different times without applying an electromagnetic field, B1 is a composite nanozyme material marked at different times without applying an electromagnetic field, C1 is a superposition of two figures in A1 and B1, A2 is a blue cell nucleus marked at different times when an electromagnetic field is applied, B2 is a composite nanozyme material marked at different times when an electromagnetic field is applied, and C2 is a superposition of two figures in A2 and B2. It can be seen that in the GL261 cells of the group without applying an electromagnetic field, no red fluorescence signal was observed at 0h and 2h. Although fluorescence signals were observed at 4 and 6h, the signal intensity did not appear to be too strong. At the same time, compared with the group without applying AMF, obvious red fluorescence signals were detected in the GL261 cells of the AMF group, and the signal intensity increased significantly with the extension of time. This shows that under the action of magnetic heat, the composite nanozyme can effectively cross the BBB and enrich in tumor cells.

[0200] Experimental Example 8

[0201] Collect the digested GL261 cells and dilute the cell suspension to 2.5 × 10 4 / mL. Then add 1.5mL of cell suspension to each well in a 3cm cell culture dish, set up 3 replicate wells in each group, shake evenly, place in a 5% CO2 cell culture incubator, incubate overnight at 37°C, remove the old culture medium, and process according to the following steps. In this experimental example, the thiazolyl blue reagent (MTT) was purchased from Bioss.

[0202] Group 1 injected the cultured cell suspension into a culture medium containing PBS buffer, placed it back in a 5% CO2 cell culture incubator, and incubated at 37°C for 24h. Then, 200μL of MTT solution (5mg / mL) was added to each well and incubated at 37°C for another 4h. Finally, the culture medium was removed, 2000μL of DMSO solution was added to each well, and the incubation continued for 30min. After shaking evenly, 200μL was taken in a 96-well plate, and the absorbance at 490nm was measured by an enzyme-linked immunosorbent assay.

[0203] Group 2 injected the cultured cell suspension into a culture medium containing 50 μM H2O2, sealed the cell culture dish, placed it in a magnetic thermal device with f=498kHz and H=1.38mT for 10 minutes, and then placed it in a 5% CO2 cell culture incubator and incubated at 37°C for 24 hours. Then, 200 μL of MTT solution (5 mg / mL) was added to each well and incubated at 37°C for another 4 hours. Finally, the culture medium was removed, and 2000 μL of DMSO solution was added to each well, and the incubation continued for 30 minutes. After shaking evenly, 200 μL was taken in a 96-well plate, and the absorbance at 490 nm was measured by an enzyme-linked immunosorbent assay.

[0204] Group 3 injected the cultured cell suspension into a culture medium containing 200ug / mL of the composite nanozyme prepared in Example 1, placed it back in a 5% CO2 cell culture incubator, and incubated at 37°C for 24h. Then, 200μL of MTT solution (5mg / mL) was added to each well and incubated at 37°C for 4h. Finally, the culture medium was removed, 2000μL of DMSO solution was added to each well, and the incubation continued for 30min. After shaking evenly, 200μL was taken in a 96-well plate, and the absorbance at 490nm was measured by an enzyme-linked immunosorbent assay;

[0205] Group 4 injected the cultured cell suspension into a medium containing 200ug / mL of the composite nanozyme prepared in Example 1 and 50μM H2O2, and placed it back in a 5% CO2 cell culture incubator and incubated at 37°C for 24h. Then, 200μL of MTT solution (5mg / mL) was added to each well and incubated for another 4h at 37°C. Finally, the culture medium was removed, 2000μL of DMSO solution was added to each well, and the incubation continued for 30min. After shaking evenly, 200μL was taken in a 96-well plate, and the absorbance at 490nm was measured by an enzyme-linked immunosorbent assay.

[0206] Group 5 is to inject the cultured cell suspension into the culture medium containing 200ug / mL of the composite nanozyme prepared in Example 1, seal the cell culture dish, place it in a magnetic thermal device with f=498kHz and H=1.38mT for 10min, and then place it in a 5% CO2 cell culture incubator and incubate it at 37°C for 24h. Then add 200μL of MTT solution (5mg / mL) to each well and continue incubating at 37°C for 4h. Finally, remove the culture medium, add 2000μL of DMSO solution to each well, continue incubating for 30min, shake evenly, take 200μL in a 96-well plate, and measure its absorbance at 490nm by enzyme-linked immunosorbent assay;

[0207] Group 6 is to inject the cultured cell suspension into a medium containing 200ug / mL of the composite nanozyme prepared in Example 1 and 50μM H2O2. After the cell culture dish is sealed, it is placed in a magnetic thermal device with f=498kHz and H=1.38mT for 10min, and then placed in a 5% CO2 cell culture incubator and incubated at 37°C for 24h. Then 200μL of MTT solution (5mg / mL) was added to each well and incubated at 37°C for another 4h. Finally, the culture medium was removed, 2000μL of DMSO solution was added to each well, and the incubation continued for 30min. After shaking evenly, 200μL was taken in a 96-well plate, and the absorbance at 490nm was measured by an enzyme-linked immunosorbent assay.

[0208] According to the instructions of the Bio-Tech GSH and GSSG detection kit, the changes in glutathione content in tumor cells of Groups 1 to 6 after treatment with different conditions were detected by enzyme-linked immunosorbent assay.

[0209] The changes in the content of ferroptosis-related lipid peroxidation (LPO) in GL261 cells from groups 1 to 6 treated with different conditions were detected using a commercial MDA kit (product number S0131S).

[0210] Results Fig.14 The cell survival rate after 24 hours of co-incubation of 200 mg / mL composite nanozymes and GL261 cells under different treatment conditions is shown. The cell survival rate after treatment with composite nanozymes alone is higher than 85%, indicating that the composite nanozymes have excellent biosafety. In the presence of hydrogen peroxide, the composite nanozymes can catalyze hydrogen peroxide to produce highly toxic hydroxyl radicals to kill tumor cells, so the survival rate of tumor cells treated with composite nanozymes and hydrogen peroxide dropped to 62.3%. Under the joint action of composite nanozymes, the cell survival rate of GL261 was 45.2%, which is mainly due to the fact that composite nanozymes can generate local high heat in electromagnetic fields to induce apoptosis of tumor cells. In the presence of composite nanozymes and hydrogen peroxide, the survival rate of tumor cells treated with AMF was less than 12%, which shows that the synergistic effect of magnetic heat therapy and chemodynamic therapy based on composite nanozyme peroxidase can effectively kill tumor cells.

[0211] Depend on Fig.15 It can be seen that the GSH content in tumor cells treated with composite nanozymes was significantly decreased, while the GSH content in tumor cells treated with hydrogen peroxide and AMF was the lowest, which indicates that MoFe2O4@CeO2 / FA can effectively consume GSH in tumor cells, and can further consume GSH in tumor cells under the action of magnetothermal effect and enzyme catalytic cascade.

[0212] Test results such as Fig.16As shown, compared with the control group, all treatment groups after treatment with the composite nanozyme showed significant LPO levels, which indicates that the composite nanozyme can effectively trigger ferroptosis of tumor cells. Fig.16 Under the action of magnetothermal effect, the LPO level of the final group was further increased, proving that the ferroptosis of tumor cells was enhanced under the action of magnetothermal effect.

[0213] Experimental Example 9

[0214] GL261-Luc cells were injected into the brains of 30 5-6 week old C57BL / 6J female mice using a stereotaxic device to construct an orthotopic glioblastoma model (model construction method reference: Small2024,2400630).

[0215] Seven days after the establishment of the orthotopic glioblastoma model, the mice were treated according to the following group settings, with 6 mice in each group;

[0216] Group 1 was injected with 200 μL of PBS buffer via the tail vein;

[0217] Group 2 placed mice in a magnetic thermal device with f = 498 kHz, H = 1.38 mT for 10 min;

[0218] Group 3 was injected with 200 μL of composite nanozyme PBS dispersion via tail vein, wherein the composite nanozyme concentration in the composite nanozyme PBS dispersion was 1.5 mg / mL;

[0219] Group 4 was injected with 200 μL of composite nanozyme PBS dispersion through the tail vein, and a magnet was tied to the mouse brain. The magnet was round 0.03T, 1 cm in diameter and 0.2 cm in thickness. The composite nanozyme concentration in the composite nanozyme PBS dispersion was 1.5 mg / mL.

[0220] Group 5 was injected with 200 μL of composite nanozyme PBS dispersion through the tail vein, and a magnet was tied to the mouse brain. The magnet was round and 0.03T, with a diameter of 1 cm and a thickness of 0.2 cm. The composite nanozyme concentration in the composite nanozyme PBS dispersion was 1.5 mg / mL. The mouse was placed in a magnetic thermal device with f=498 kHz and H=1.38 mT for 10 min.

[0221] The T1 and T2 signals of the brains of mice in groups 4 and 5 were detected by clinical 3.0T magnetic resonance imaging equipment. Fig.17It can be seen that for mice not treated with AMF, within 3 hours (the time for magnetic heat to open the BBB is 3 hours, which has been reported in the literature), no obvious T1 and T2 signal changes were observed in the brain tumor area of ​​the mice. However, for mice pretreated with AMF (f = 498kHz, H = 1.38mT magnetic heat device treatment for 10 minutes), obvious T1 and T2 signal changes were observed in the brain tumor area, which shows that the combination of dual targeting and magnetic heat can effectively break through the BBB restriction, proving that the composite nanozyme can be used as an MRI dual-modality contrast agent for the detection of early glioblastoma.

[0222] After tail vein administration, 3 mg of D-luciferin potassium salt was dispersed in 200 μL PBS to obtain D-luciferin potassium salt solution, and the prepared D-luciferin potassium salt solution was injected into the mouse peritoneum (200 μL of D-luciferin potassium salt solution was injected into each mouse), and the bioluminescent signal was measured by the in vivo imaging device AniView Phonenix 600SE to obtain the bioluminescent signal of the mouse brain during different treatment periods to monitor the growth of the tumor, such as Fig.18 As shown, during the treatment period, the bioluminescence signal of the brain of mice in Group 1 that only used PBS buffer gradually increased, indicating the normal growth of the tumor. Compared with Group 1, the bioluminescence signal of mice injected with composite nanozymes decreased. This may be because the smaller size of the composite nanozymes is conducive to its partial penetration of the BBB and effective enrichment at the tumor site. The group pre-treated with magnetic heat showed obvious tumor growth inhibition. In the final group, no obvious bioluminescence signal was observed within two days after the end of treatment, which shows that the synergy of chemodynamic therapy and magnetic heat therapy triggered by composite nanozymes under dual targeting effectively inhibited and eliminated glioblastoma. Fig.18 The scale size is 50 μm.

[0223] On the 14th day of tumor treatment (the day of composite nanozyme injection was regarded as day 0), the mice were killed and the brains containing tumors were collected and paraffin sliced. Immunohistochemical staining was performed after the tumor slices were dewaxed. Fig.19 As shown in the figure, the content of LPO in the control group was low, while the content of LPO in the group containing composite nanozymes after AMF pretreatment was high, which indicates that after the composite nanozymes were enriched in the tumor site, they increased the content of LPO in tumor cells, causing ferroptosis of tumor cells. Therefore, the composite nanozymes significantly improved their multi-enzyme catalytic activity under the action of magnetic heat, effectively inducing ferroptosis of tumors.

[0224] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the invention.

Claims

1. A composite nanozyme, characterized in that: The structure of the composite nanozyme includes a core material and a cerium oxide shell layer coated on the outer layer of the core, wherein the core material includes ferrite, and the chemical formula of the ferrite is MoFe2O4. The structure of the composite nanozyme also includes an active targeting ligand coated on the surface of the shell layer, wherein the active targeting ligand is folic acid. The preparation method of the composite nanozyme comprises the following steps: S1, in the presence of a first organic solvent, mixing ferric acetylacetonate, molybdenum acetylacetonate and a surfactant, and heating the mixture in an inert atmosphere to obtain a core material, wherein the surfactant is oleic acid; S2, mixing the core material, cerium acetylacetonate and a surfactant, and heating them in an inert atmosphere to obtain a composite nanozyme solution, wherein the surfactant is oleic acid; The method for preparing the composite nanozyme further comprises the step of mixing the composite nanozyme solution with the folic acid solution.

2. The composite nanozyme according to claim 1, characterized in that The structure of the composite nanozyme also includes a drug arranged on the cerium oxide shell layer.

3. A method for preparing the composite nanozyme according to any one of claims 1 to 2, characterized in that: The following steps are included: S1, in the presence of a first organic solvent, mixing ferric acetylacetonate, molybdenum acetylacetonate and a surfactant, and heating the mixture in an inert atmosphere to obtain a core material, wherein the surfactant is oleic acid; S2, mixing the core material, cerium acetylacetonate and a surfactant, and heating them in an inert atmosphere to obtain a composite nanozyme solution, wherein the surfactant is oleic acid; The method for preparing the composite nanozyme further comprises the step of mixing the composite nanozyme solution with the folic acid solution.

4. The preparation method according to claim 3, characterized in that: The temperature of the heating treatment is 200-300° C., and the heating time is 2-12 hours.

5. The method for preparing the composite nanozyme according to claim 4, characterized in that: The step of heating treatment in step S1 and / or step S2 comprises reacting at a first temperature for a first time, then heating to a second temperature for a second time; and / or, The first organic solvent includes at least one of octadecene, tetradecene or benzyl ether.

6. The method for preparing the composite nanozyme according to claim 5, characterized in that: The first temperature is 200-220° C., and the first time is 1-1.5 hours; and / or, The second temperature is 290-310° C., and the second time is 0.5-1.5 h; and / or, Before the heating treatment in step S1, the method further includes heating the mixed solution formed by mixing ferric acetylacetonate, molybdenum acetylacetonate, the first organic solvent and a surfactant to 110-120° C. and maintaining the mixture for 30-60 minutes in an inert atmosphere, wherein the surfactant is oleic acid; Before the thermal decomposition reaction in step S2, the method further includes heating the mixture formed by mixing the core material with cerium acetylacetonate and oleic acid to 110-120° C. and maintaining the mixture for 30-60 minutes in an inert atmosphere. Before mixing the core material with cerium acetylacetonate and a surfactant, the temperature of the core material is adjusted to 100-120° C., wherein the surfactant is oleic acid.

7. The method for preparing the composite nanozyme according to claim 6, characterized in that: The molar ratio of ferric acetylacetonate, molybdenum acetylacetonate, surfactant and organic solvent in step S1 is (1-2):1:(5-10):(50-100), wherein the surfactant is oleic acid; and / or, The molar ratio of the iron acetylacetonate in step S1 to the cerium acetylacetonate in step S2 is (1-2): (1-2).

8. The preparation method according to claim 7, characterized in that: The composite nanozyme solution comprises a mixture of the composite nanozyme and a second organic solvent, The active targeting ligand solution includes a mixture of folic acid, an alkaline substance and a second organic solvent, wherein the alkaline substance includes sodium hydroxide, The second organic solvent in the composite nanozyme solution and / or the active targeting ligand solution includes at least one of cyclohexane, chloroform, acetone, toluene or ethanol. The mass ratio of the alkaline substance to folic acid is 1:(15-30), The mass ratio of the composite nanozyme to folic acid is 1:(5~10).

9. A composite nanozyme according to any one of claims 1 to 2 or a composite nanozyme prepared by the composite nanozyme preparation method according to any one of claims 3 to 8 having any of the following uses: (1) Use in the preparation of tumor diagnostic reagents; (2) Use in the preparation of products for treating tumors.

Citation Information

Patent Citations

  • Fe3O4-MnO2-CeO2 nano material as well as preparation method and application thereof

    CN114797889A

  • Multifunctional cascade nano-enzyme as well as preparation method and application thereof

    CN115888773A